(untitled) - Ghosh, A. (Chischester, 1986)
Material properties play a key role in manufacturing processes. This volume therefore starts with a discussion on these properties. This is followed by a detailed analysis of the various processes, namely, casting, forming, machining, and joining.
Công nghệ phục hồi chi tiết máy
Keywords: Production engineering